Intraspecific variation in recent populations of Globigerinoides ruber from the eastern Indian Ocean: evidence from test morphology and geochemistry - Sadekov, Aleksey Yu; Eggins, Stephen M.; Deckker, Patrick De (Anuário do Instituto de Geociências, 2006)
Abstract